Acumulação capitalista, regulação do trabalho e agronegócio no Brasil: uma relação de dependência e subdesenvolvimento - Yasmin Silveira Martins (2023)
The present paper's research problem is to answer whether it is possible to achieve the so-called capitalist economic development in Brazil by intensifying the productive dynamics of agribusiness in the country. It aims to demonstrate that such conduct only accentuates the condition of Brazilian dependence, common to Latin American countries, in relation to the global center, given the fact that this productive model is a modern source of capital accumulation. It can be seen that, due to the dynamics of plundering introduced in Brazil since colonization, the country was inserted in a cycle of dependence with the global center, functionalizing its capitalist development, in such a way that the condition of underdevelopment of Brazil, as a Latin American country, is nothing more than the dynamics that was generated as a consequence of the capitalist development of the center of capital itself, not a stage of development. It is demonstrated that agribusiness causes severe impacts on the Brazilian socio-environmental reality, since the dynamics under which its production is developed are necessarily based on the overexploitation of labor and destruction of the environment, whether through the excessive use of chemicals (fertilizers and pesticides) or through deforestation and constant occupation of new spaces to extend the areas destined to monocultures for export. Moreover, it is observed that these circumstances are greatly corroborated and made possible by the great influence that agribusiness exerts on Brazilian institutions and politics, with wide participation in the National Congress and strong media appeal. Therefore, we conclude that Brazilian agribusiness will not lead Brazil to capitalist economic development, because it has a great impact on the production and reproduction of inequalities in the countryside, as well as on the overexploitation of rural workers, affecting their quality of life and weakening the labor relations that develop under this productive model. In addition, although agribusiness appears as a kind of philosopher's stone of Brazilian development, it is exposed that it contributes little to the generation of wealth and to the economic growth of the country through the generation of revenues for the public coffers. To this end, the legal-sociological methodological approach is used in this research, as well as the sociological analysis method coined by Marx and Engels, the historical-dialectical materialism.